Expression transformation of claudin-1 in the process of gastric adenocarcinoma invasion - Wu, Yong-Lian (The WJG Press and Baishideng, 2008)
AIM: To investigate the relation of expression transformation of claudin-1 with invasiveness and metastasis of gastric carcinoma. METHODS: By using immunohistochemistry, expression of claudin-1 in mucosa and invasive front of 136 gastric adenocarcinoma cases and proliferative index (Ki-67) were detected and analyzed. RESULTS: In mucosa, the claudin-1 over-expression rate of mucinous adenocarcinomas (including signet-ring cell carcinomas) was the highest. It was negatively related with the differentiation but positively related with the invasiveness and metastasis of gastric cancer. In invasive front, the claudin-1 over-expression rate was positively related with the differentiation, invasiveness and metastasis of gastric carcinoma. The expression transformation of claudin-1 was found in gastric carcinoma. The expression of claudin-1 in invasive front was transformed in 28/136 gastric carcinoma cases. The transformation rate in highly differentiated tubular adenocarcinomas was the highest (51.5%, 17/33). The deeper was the invasiveness, the higher was the transformation rate. The claudin-1 expression transformation rate in serosa and omenta was significantly higher (92.9%) than in tunica muscularis of invasive gastric cancer cases, as well as in patients with lymph node metastasis than in those without lymph node metastasis. CONCLUSION: Up-regulation of claudin-1 expression and its transformation in invasive and metastatic gastric carcinoma suggest that claudin-1 participates in the transformation of biological behaviors in neoplasms. Further study is needed to elucidate the precise mechanism and the relation of claudin-1 expression with the neoplasm progress.